(untitled) (City: History, Culture, Society, 2021)
The paper analyzes data on one of the groups of zooarchaeological material, namely, bird eggs, from the Chernyakhiv − Sîntana-de-Mureş Culture’s graves. Bird eggs were found in 111 burial complexes, which is 2 % of the total number of culture’s burials. Eggs of different species of birds are represented in the burials, but chicken prevails. Their number in burials ranges from one to 12, the location in the space of the grave is not unified. Eggs are present in the burials of women and men of different age groups, but more often in children’s burials. The practice of laying eggs in burials is observed practically over the entire territory of the distribution of culture, but the highest concentration falls on the Northern Black Sea coast. Obviously, it is from this region that tradition originates. The eggs in the graves are fixed, starting from the second stage of the existence of culture. There are fewer of them in burials with a western orientation, which is considered late. In most cases (97 %), eggs were found in burials with a northern orientation, which makes them not considered as part of the Christian paraphernalia. The tradition of laying eggs in burials most likely came from the ancient world − they have long been present in ancient necropolises. The highest concentration of eggs in the graves of Chernyakhov culture is observed precisely in those regions that border the ancient world and where the Hellenes were part of the culture carriers. It is possible that the eggs could be not only parting food but could carry certain semantic loads (used to cleanse and play the role of an apotropa). The egg in the ancient world was associated with the ideas of rebirth, immortality and resurrection (cults of Dionysus and Asclepius), evidently in demand in the then society.